2014
DOI: 10.7883/yoken.67.428
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Thwaites' Diagnostic Scoring System for the Differential Diagnosis of Tuberculous Meningitis and Bacterial Meningitis

Abstract: SUMMARY:To compare the clinical features of patients with tuberculous meningitis (TBM) and bacterial meningitis (BM) and to validate Thwaites' diagnostic scoring system for the differential diagnosis of TBM and BM, a retrospective review of 211 patients with TBM or BM who were admitted to Huashan Hospital, Fudan University, from 2007 to 2012 was conducted. The clinical characteristics and laboratory data were compared, and Thwaites' diagnostic scores were assessed at the time of admission for the differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
1
11
0
2
Order By: Relevance
“…Mustafa Sunbul et al evaluated Thwaites' score and sensitivity and specificity to diagnose TBM were 95% and 70% respectively [4]. In our study if only TBM and pyogenic meningitis were included for analysis (excluding cryptococcal meningitis etc), sensitivity and specificity of Thwaites' score to diagnose TBM were 96% and 70% respectively which was very similar to the findings of Mustafa Sunbul et al Zhang et al reported a sensitivity and specificity of 98.2 % and 43.6 % respectively [5]. In a study published by Roshin Kurien et al, Thwaites' score compared well with Lancet consensus score in diagnosing TBM.…”
Section: Discussionsupporting
confidence: 85%
“…Mustafa Sunbul et al evaluated Thwaites' score and sensitivity and specificity to diagnose TBM were 95% and 70% respectively [4]. In our study if only TBM and pyogenic meningitis were included for analysis (excluding cryptococcal meningitis etc), sensitivity and specificity of Thwaites' score to diagnose TBM were 96% and 70% respectively which was very similar to the findings of Mustafa Sunbul et al Zhang et al reported a sensitivity and specificity of 98.2 % and 43.6 % respectively [5]. In a study published by Roshin Kurien et al, Thwaites' score compared well with Lancet consensus score in diagnosing TBM.…”
Section: Discussionsupporting
confidence: 85%
“…Their evaluation revealed the sensitivity and specificity of the system to be 95.6 and 70.8%, respectively. Zhang et al evaluated Thwaites scoring system and concluded to be highly effective for the differential diagnosis of TBM and initially treated bacterial meningitis but were found to be less effective for that of TBM and partially treated bacterial meningitis [13]. J.…”
Section: Discussionmentioning
confidence: 99%
“…S Sebastian et al evaluated Thwaites scoring system in 527 patients (adults and pediatrics), and concluded that the scoring system was sensitive but not specific when used to distinguish TBM from bacterial meningitis in HIV negative adults. In HIV positive adults the index had low diagnostic accuracy [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, diagnosis of TBM depended on various tests including X-pert MTB/rifampicin (RIF) and IGRA 12 27 28 and clinical criteria. 11 13 29 30 However, the diagnostic sensitivity and specificity of these tests vary from one dataset to another. TB culture of the CSF is still accepted as the only confirmatory test.…”
Section: Discussionmentioning
confidence: 99%